RETRACTED: Building the inflower and realizing seed productivity of A.giganteum regel - Uralov Abdumannon; Mustafakulov Mukhammadjon; Mamatkulova Iroda; Sattorova Madina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001